THE EFFECT OF USING STAND UP SEQUENCE GAME TOWARD STUDENTS’ VOCABULARY MASTERY OF BUDI UTOMO ENGLISH CLUB OF METRO IN 2020/2021 ACADEMIC YEAR - Betty Apri Centrawati; Amirudin Latif (Journal of English Education and Enterpreneurship (JEEP), 2021)
The study is aimed to find out whether the use of Stand upSequence Game is effective as the media in teaching vocabularymastery. The study used quasi-experimental design with the researchpopulation namely 22 female students of Budi Utomo Orphanage. The researcher conducted the systematic of purposive samplingand used pre-test and post-test as a research instrument. To analyze thepre-test and post-test score, the researcher used t-test analyzes. Theresult of the first hypothesis test which uses 5% significant degree, wherethe t-test obtained is (6.999) which also higher than that of t table (2.22).The second hypothesis test where the t-test obtained is (2.274) which ishigher than that of t table (2.08). It shows that the students who are taughtby Stand up Sequence Game having a higher score. In conclusion, thatteaching English vocabulary using Stand up Sequence Game is moreeffective than that of without using Stand up Sequence Game.